Wavelet decomposition and embeddings of generalised Besov–Morrey spaces - Haroske, Dorothee D. (2022)
We study embeddings between generalised Besov–Morrey spaces Nφ,p,qs(Rd). Both sufficient and necessary conditions for the embeddings are proved. Embeddings of the Besov–Morrey spaces into the Lebesgue spaces Lr(Rd) are also considered. Our approach requires a wavelet characterisation of the spaces which we establish for the system of Daubechies wavelets. © 2021 The Author(s)